2003
DOI: 10.1590/s0103-166x2003000100001
|View full text |Cite
|
Sign up to set email alerts
|

Stress Infantil e Desempenho Escolar: avaliação de crianças de 1ª a 4ª série de uma escola pública do município de São Paulo

Abstract: O objetivo deste trabalho foi caracterizar o stress em crianças de 1ª a 4ª série, de uma escola pública do município de São Paulo e ainda comparar a presença ou ausência do stress com o respectivo desempenho escolar, das crianças. 342 crianças foram avaliadas pela Escala de Stress Infantil (ESI). O desempenho escolar das crianças foi obtido a partir da média de conceitos (A, B, C, D e E) fornecidos pelos professores, em sete disciplinas. E, para fins de tratamento estatístico, o desempenho escolar passou a se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
2
6
0
5
Order By: Relevance
“…Given the obtained results in this study in which there were no statistically significant differences in the stress level among children with and without SLD, nor between boys and girls, these results were also observed in previous studies 12,13,17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Given the obtained results in this study in which there were no statistically significant differences in the stress level among children with and without SLD, nor between boys and girls, these results were also observed in previous studies 12,13,17 .…”
Section: Discussionsupporting
confidence: 90%
“…A study 13 that evaluated 342 children at a school in São Paulo also found no statistically significant differences between the groups with and without school failure, corroborating the results of our study. Although, only 30% of the studied children showed stress signs, and of these, 38.2% were indicated as having poor school performance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the frequency of extracurricular activities and life experiences contribute to the presence or absence of stress in children, manifesting itself in school difficulties. In general, the percentage of stressed children is usually higher in the groups with poor school performance (27) . Students reporting more number of practices of social activities obtained, in this research, better performance than others in the reading of frequent words.…”
Section: Discussionmentioning
confidence: 99%
“…O estresse infantil também está relacionado com os sintomas citados anteriormente, uma vez que o mesmo com intensidade excessiva e prolongada pode levar a problemas graves de saúde, como distúrbios ansiosos, depressão, entre outros problemas de saúde física e mental (Lemes et al, 2003). No entanto, apesar das diferenças significativas encontradas com os escores de depressão, não foram observadas tais diferenças na variável estresse.…”
Section: Discussionunclassified